2007
DOI: 10.1016/j.expneurol.2007.08.020
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol protects the neonatal brain from hypoxia–ischemia

Abstract: Hypoxia-ischemia is relatively common in human infants. Hypoxia-ischemia can occur as a result of complications associated with prematurity or birth, frequently leading to altered brain development and cognitive and behavioral deficits that persist throughout life. Despite the relative frequency of neonatal hypoxic ischemic encephalopathy, the immature brain sustains relatively less damage than an adult who experiences a similar crisis of oxygen and nutrient deprivation. Therefore, factors may be present that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 71 publications
(85 reference statements)
0
30
0
3
Order By: Relevance
“…Finally a total of 66 studies were included, of which 56 concluded that estrogens exerted a protective effect (Alkayed et al, , 2000Amantea et al, 2007;Bagetta et al, 2004;Chiappetta et al, 2007;Choi et al, 2004;Dai et al, 2007;Dubal et al, 1998Dubal et al, , 2006Dubal and Wise, 2001;Dziennis et al, 2007;Fan et al, 2003;Feng et al, 2005;Fukuda et al, 2000;Green et al, 2001;Gulinello et al, 2006;Hawk et al, 1998;He et al, 2002;Jover-Mengual et al, 2007;Kii et al, 2005;Koh, 2007Koh, , 2008Koh, , 2006Littleton-Kearney et al, 2005;Liu et al, 2007Liu et al, , 2002McCullough et al, 2001;Miller et al, 2005;Nunez et al, 2007;O'Donnell et al, 2006;Pelligrino et al, 1998;Plamondon et al, 2006;Rau et al, 2003;Raval et al, 2007;Ritz et al, 2004;Rusa et al, 1999;Saleh et al, 2004Saleh et al, , 2001aSandstrom and Rowan, 2007;Schreihofer et al, 2005;Shi et al, 2001Shi et al, , 1997Simpkins et al, 1997;…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Finally a total of 66 studies were included, of which 56 concluded that estrogens exerted a protective effect (Alkayed et al, , 2000Amantea et al, 2007;Bagetta et al, 2004;Chiappetta et al, 2007;Choi et al, 2004;Dai et al, 2007;Dubal et al, 1998Dubal et al, , 2006Dubal and Wise, 2001;Dziennis et al, 2007;Fan et al, 2003;Feng et al, 2005;Fukuda et al, 2000;Green et al, 2001;Gulinello et al, 2006;Hawk et al, 1998;He et al, 2002;Jover-Mengual et al, 2007;Kii et al, 2005;Koh, 2007Koh, , 2008Koh, , 2006Littleton-Kearney et al, 2005;Liu et al, 2007Liu et al, , 2002McCullough et al, 2001;Miller et al, 2005;Nunez et al, 2007;O'Donnell et al, 2006;Pelligrino et al, 1998;Plamondon et al, 2006;Rau et al, 2003;Raval et al, 2007;Ritz et al, 2004;Rusa et al, 1999;Saleh et al, 2004Saleh et al, , 2001aSandstrom and Rowan, 2007;Schreihofer et al, 2005;Shi et al, 2001Shi et al, , 1997Simpkins et al, 1997;…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Frühgebo-rene werden abrupt diesem Milieu entzogen. Östradiol schützt im Tierexperiment das unreife Gehirn vor hypoxisch-ischä-mischen Läsionen ( [24,25]; . Abb.…”
Section: Stammzellenunclassified
“…Эстрадиол в дозе 100 мг/кг при вве-дении в первые 3 ч после повреждения эффективно защи-щает кору (зона повреждения сокращается более чем на 50%), тогда как при увеличении времени задержки терапии до 6 ч эффективны лишь более высокие дозы (500 и 1000 мг/кг). В опытах на новорожденных грызунах показано, что однократное введение эстрадиола не влияет на повреждение мозга, тогда как троекратное его введение имеет достоверный нейропротекторный эффект [50].…”
Section: нейропротекторная активность эстрадиолаunclassified
“…Эстрогены проявляют защитные эффекты в моделях токсического и ишемического повреждения ЦНС: при глутаматной эксайтотоксичности (мембранные, РЭα, снижение уровня mGluR1 [50]); при аутоиммунном энце-фаломиелите (GPER1) [51]; при рассеянном склерозе [52]; при каинатной, метамфетаминовой, алкогольной и глюкокортикоидной токсичности [53]; при колхици-новом повреждении мозга, гипоксическом повреждении развивающихся олигодендроцитов (РЭα и РЭβ) [54]. Так, высокий уровень экзогенных и эндогенных эстро-генов может задерживать развитие симптомов рассеян-ного склероза [52].…”
Section: нейропротекторная активность эстрадиолаunclassified